Factor XIII-guided treatment algorithm reduces blood transfusion in burn surgery - João Miguel Gonçalves Valadares de Morais Carneiro; Joana Alves; Patrícia Conde; Fátima Xambre; Emanuel Almeida; Céline Marques; Mariana Luís; Ana Maria Mano Garção Godinho; Fernando Fernandez-Llimos (Brazilian Journal of Anesthesiology, 2018)
Background and objectives: Major burn surgery causes large hemorrhage and coagulation dysfunction. Treatment algorithms guided by ROTEM® and factor VIIa reduce the need for blood products, but there is no evidence regarding factor XIII. Factor XIII deficiency changes clot stability and decreases wound healing. This study evaluates the efficacy and safety of factor XIII correction and its repercussion on transfusion requirements in burn surgery. Methods: Randomized retrospective study with 40 patients undergoing surgery at the Burn Unit, allocated into Group A those with factor XIII assessment (n = 20), and Group B, those without assessment (n = 20). Erythrocyte transfusion was guided by a hemoglobin trigger of 10 g.dL−1 and the other blood products by routine coagulation and ROTEM® tests. Analysis of blood product consumption included units of erythrocytes, fresh frozen plasma, platelets, and fibrinogen. The coagulation biomarker analysis compared the pre- and post-operative values. Results and conclusions: Group A (with factor XIII study) and Group B had identical total body surface area burned. All patients in Group A had a preoperative factor XIII deficiency, whose correction significantly reduced units of erythrocyte concentrate transfusion (1.95 vs. 4.05, p = 0.001). Pre- and post-operative coagulation biomarkers were similar between groups, revealing that routine coagulation tests did not identify factor XIII deficiency. There were no recorded thromboembolic events. Correction of factor XIII deficiency in burn surgery proved to be safe and effective for reducing perioperative transfusion of erythrocyte units. Resumo: Justificativa e objetivos: A cirurgia no grande queimado causa hemorragia de grande porte e disfunção da coagulação. Os algoritmos de tratamento guiados por ROTEM® e fator VIIa reduzem as necessidades de hemoderivados, mas falta evidência em relação ao fator XIII. A deficiência do fator XIII altera a estabilidade do coágulo e diminui a cicatrização. Este estudo avalia a eficácia e a segurança da correção do fator XIII e sua repercussão nas necessidades transfusionais na cirurgia do queimado. Métodos: Estudo retrospectivo randomizado de 40 doentes submetidos à cirurgia na Unidade de Queimados alocados em grupo A com estudo do fator XIII (n = 20) e grupo B sem estudo (n = 20). A transfusão eritrocitária foi guiada por gatilho de hemoglobina de 10 g.dL−1 e os outros hemoderivados por testes de coagulação de rotina e ROTEM®. A análise do consumo de hemoderivados incluiu unidades de eritrócitos, plasma fresco congelado, plaquetas e fibrinogênio. A análise dos biomarcadores da coagulação comparou os valores pré e pós-operatórios. Resultados e conclusões: O grupo A (com estudo de fator XIII) e o grupo B apresentaram área de superfície corporal total queimada idêntica. Todos os doentes do grupo A revelaram déficit pré-operatório de fator XIII, cuja correção reduziu significativamente a transfusão de unidades de concentrado eritrocitário (1,95 vs. 4,05, p = 0,001). Os biomarcadores de coagulação pré e pós-operatórios foram semelhantes entre os grupos, revelaram que os testes de coagulação de rotina não identificam o déficit de fator XIII. Sem eventos tromboembólicos registrados. A correção do fator XIII na cirurgia do queimado revelou-se segura e eficaz na redução da transfusão perioperatória de unidades de eritrócitos. Keywords: Intensive care, Burned, Surgery, Coagulation and hemostasis, Factor XIII, Palavras-chave: Cuidados intensivos, Queimados, Cirurgia, Coagulação e hemostase, Fator XIII